Analisis Penilaian Konsumen Terhadap Ekuitas Merek Ayam Geprek Di Kota Serang - Rodiatul Ulfah,; Meita Rahayu,; Syamsul Hidayat, (Student Scientific Creativity Journal, 2024)
This research was conducted to measure the brand equity of four geprek chickens in Serang, namely Geprek Bensu Serang Timur, Ayam Geprek Bun Bun Pakupatan Serang, Ayam Geprek Panglima, and Ayam Geprek Labbaik Chicken Pakupatan Serang. The population in this study were Geprek Chicken consumers in Serang. Using Aaker’s 4 variable method, namely brand awareness, brand association, impression of quality, and brand loyalty. The results of this research revealed that Ayam Geprek Bensu east Serang had the brand awareness that was most remembered by respondents, the brand association for Ayam Geprek Bensu east Serang was the most positive, and brand loyalty was the highest. Meanwhile, Ayam Geprek Labbaik Chicken has the impression of the best quality.